Implementation and evaluation of clinical supervision for support workers in a paediatric palliative care setting. (April 2022) - Beavis, Jonathan; McKenzie, Sian; Davis, Lucy; Ellison, Nell
Support workers represent a large proportion of the NHS workforce and yet their supervisory needs are often overlooked. This study focused specifically on a cohort of support workers in a community paediatric palliative care setting. Peer supervision was implemented for this group, initially face to face and then virtually. The experiences of clinical supervision for this group were investigated through responses to an online survey ( n = 25) and two focus groups ( n = 7). Survey data were analysed concurrently with a thematic analysis. The following themes and sub-themes were developed from transcribed focus groups: (1) Barriers to engagement (2) Being Listened to (3) What Worked Well: Logistics. Overall, delivery of supervision was effective to a mixed degree – though support workers appreciated a space to be listened to, their distrust of colleagues and other barriers impeded the capacity of supervision to achieve more than support and catharsis for this group. Future projects should focus on introducing more preliminary interventions to promote reflection and peer support for these groups as well as continue to consider the supervisory needs of support workers.